1993
DOI: 10.1021/bi00079a017
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman and optical transient studies on the light-induced proton pump of bacteriorhodopsin reveal parallel photocycles

Abstract: The photocycle of bacteriorhodopsin (bR) was studied at ambient temperature in aqueous suspensions of purple membranes using time-resolved resonance Raman (RR) and optical transient spectroscopy (OTS). The samples were photolyzed, and the fractional concentrations of the retinylidene chromophore in its parent state, BR570, and in the intermediate states L550, M412, N560, and O640 were determined in the time domain 20 microseconds-1 s and in the pH range 4-10.5. Two kinetically different L components could be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 95 publications
4
79
1
Order By: Relevance
“…A decrease of absorbance is due to proton release into the suspension; an increase of absorbance is due to proton uptake. Traces 1-5 were taken at pH 6.0, 6.3, 6.5, 6.8, and 7.0. with a pK a of 7.2 seen in the WT (27,(35)(36)(37)(38) and the E204Q and E194Q mutants (27) was tentatively assigned to D96 in the late N or O states (27). The reason for the decreased pK a (and decreased amount of O intermediate at neutral pH) in R134H as well as in E194D (27) should be investigated further.…”
Section: Estimations Of the Pk A Of The Proton Release Group Inmentioning
confidence: 97%
“…A decrease of absorbance is due to proton release into the suspension; an increase of absorbance is due to proton uptake. Traces 1-5 were taken at pH 6.0, 6.3, 6.5, 6.8, and 7.0. with a pK a of 7.2 seen in the WT (27,(35)(36)(37)(38) and the E204Q and E194Q mutants (27) was tentatively assigned to D96 in the late N or O states (27). The reason for the decreased pK a (and decreased amount of O intermediate at neutral pH) in R134H as well as in E194D (27) should be investigated further.…”
Section: Estimations Of the Pk A Of The Proton Release Group Inmentioning
confidence: 97%
“…More recently, it has been shown that Mf decays to the ground state through the O intermediate whereas Ms does not [4,5]. A recent study showed that very mild treatment of purple membranes (PM) with Triton X-100 destroyed the ability of actinic light to influence the photocycle and altered the decay pathway of Mf without disrupting the trimer BR structure [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the L-M transition is accelerated at alkaline pH (15,29). At low pH the O intermediate is accumulated, whereas the lifetime of the N intermediate is prolonged at high pH (15,(30)(31)(32). The sequence of proton release and uptake is reversed at a pH lower than 6 [late proton release (33,34)].…”
mentioning
confidence: 99%